TANTANG AN DAN PELUANG PEMBENTUKAN BANK BUMN SYARIAH DALAM MENYAMBUT ASEAN ECONOMIC COMMUNITY 2015 - Anna Marina; Sentot Imam Wahjono; Ezif Muhammad Fahmi (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
The aim of this  study  is to conduct  a scientific  study  on the  challenges  and opportunities  of  the  establishment   of  Islamic  banks  in  Indonesia,  which  is majority owned by the State Ownership Corporation (BUMN). During 21 years of  operation  of  Islamic  banking  in  Indonesia  accounted  for  only  5%   of  the national banking system, while it welcomed the ASEAN Community in 2015 will open  opportunities  entrants  from  foreign  countries  in the  Indonesian  banking market, especially from Malaysia, which already has a strong Islamic banks and big. Therefore  in this paper presented  are the challenges  and opportunities  in establishing  Islamic bank with PT Bank BRI Tbk convert  into sharia and was soon followed by the acquisition of three other state-owned Islamic bank so that the new Islamic bank(Bank Syariah Indonesia) has the potentialo be the largest Islamic bank in the world